COMPARISON OF THE LOCAL ANESTHETIC INJECTION AND THE LOW POWER LASER TREATMENT IN FIBROMYALGIA SYNDROME - Reyhan Tuncay,; Eda Gürçay,; Ece Alanoğlu,; Güher Yezer,; Aytül Çakcı, (Archives of Rheumatology, 2006)
Objective: Fibromyalgia syndrome (FS) is a disease characterized by pain and tender points. Various physical therapy modalities and local anesthetic (LA) injection of the tender points are used in the treatment. The aim of this study was to investigate the effects of LA injection of the tender points and low power laser (LPL) treatment on pain and other symptoms in patients with FS. Patients and Methods: A total of 30 patients diagnosed as FS according to American College of Rheumatology (ACR) were included in the study and randomised in two treatment groups. In group I. LA injection, in group II. LPL treatment of the tender points were applied. Patients were evaluated for the pain, pain in the tender points, muscle spasm, morning stiffness, insomnia and fatigue, number of tender points and Fibromyalgia Impact Questionnaire (FIQ) at baseline and 2 weeks after treatment. Results: Demografic data of the patients were similar and there was no difference between the groups before treatment. In group II after 2 weeks of treatment pain (p=0.003), pain in the tender points (p=0.004), insomnia (p=0.18) and fatigue (p=0.015), number of tender points (p=0.003) and FIQ (p=0.039) values were lower than group I. In group I, all parameters except morning stiffness and in group II all parameters were significantly lowered. Conclusion: In FS patients LA injection and LPL treatment improve pain and other disease symptoms. When both treatment modalities compared, the LPL treatment seems to improve symptoms at an earlier phase. (Rheumatism 2006; 21: 1-4)